Hiding the truth: exegetical discussions of Abraham's lie from Hugh of St. Victor to Stephen Langton. Issue 235 (16th January 2014) - Corran, Emily
Abstract: This article hopes to continue the tradition of Bible commentary scholarship initiated by Beryl Smalley by considering three exegetes from the late twelfth century who commented on Abraham's lie to the Egyptians (Genesis XII:13). Augustine's exegesis on this passage prompted Hugh of St. Victor, Peter the Chanter and Stephen Langton to consider not only whether Abraham was lying, but also the broader question of whether he was justified in deceiving by omission. All three agree with Augustine that lying is wrong, but are less willing to endorse his statement that Abraham justly hid the truth. In their discussions of Abraham's actions and motives, the exegetes put forward an understanding of dishonesty which includes misleading as well as mendacious speech and consider the role of moral obligations between people in the decision to 'hide the truth'. The ethical thought of Peter the Chanter and Stephen Langton in particular was original: both criticized Augustine's theory of lying and advocated stricter understandings of honesty at a time when other authors were less critical of Augustine's theory of licit omission. As such, they deserve to be given a place in the history of ethics.